PENCEGAHAN KEJAHATAN SIBER PADA MEDIA SOSIAL MELALUI IDENTIFIKASI BAHASA PARA PELAKU - Mulia, Adinda Jati; Firmansyah, Andrean; Purba, Claudia Dwi Anugrah; Mozi, Muhammad Farhan Adinata; Pramata, Arganta Bisma; Ilmawan, Muhammad Agist; Anugrah, Muhammad Zaky Priambada; Sholihatin, Endang (Universitas Sultan Ageng Tirtayasa, 2023)
From various cyber cases, cybercriminals employ different communication methods in each case, using language as a primary tool for committing crimes. This study aims to 1) identify the language used by cybercriminals on social media and 2) understand efforts to prevent cybercrimes on social media by identifying the language used by perpetrators. This research method utilizes a qualitative approach through literature review, data collection via observation, and documentation on social media platforms. The conclusions drawn from this study are: 1) cybercriminals on social media tend to use provocative language with sensational titles, defamation (insults) using vulgar language/words, and discriminatory language related to race, religion, and ethnicity (SARA); 2) prevention of cybercrimes on social media can be achieved by enhancing digital literacy regarding information accuracy, awareness of ethics and etiquette in using social media, utilizing social media for positive purposes, emphasizing education on social media usage, refraining from sharing personal information, understanding the risks and impacts of spreading false information, and critically analyzing news in a rational manner.